The Optical Nature of Myopic Changes in Retinal Vessel Caliber - Yii, Fabian; Strang, Niall; Moulson, Colin; Dhillon, Baljean; Bernabeu, Miguel O.; MacGillivray, Tom (Ophthalmology science (Online), 2025)
Dimensional measures of retinal features are subject to the optical influence of ocular magnification. We examined the impact of ocular magnification on the association between axial length (AL) and measurements of retinal vessel caliber in fundus photographs. Cross-sectional study. Eighty-two normal right eyes from healthy participants aged 16 to 31 years. Central retinal arteriolar and venular equivalents (CRAE and CRVE) were derived from color fundus photographs using semiautomated software. Ordinary least squares linear regression was used to assess the influence of AL (independent variable) on CRAE and CRVE, controlling for age, sex, and ethnicity, both before and after magnification correction using different formulae. These formulae estimate magnification based on different ocular parameters: AL only (Bennnett’s formula), refractive error only (Bengtsson’s formula), and refractive error combined with keratometry (Littmann’s formula). Previous research has primarily relied on Bengtsson’s formula, which is less accurate than Bennett’s formula. We also examined the impact of treating the nontelecentric fundus camera used in this study as telecentric when applying these magnification correction formulae. Central retinal arteriolar and venular equivalents (in pixels). Before magnification correction, increasing AL was associated with decreasing CRAE (β: −0.49, 95% confidence intervals: −0.89 to −0.09, P = 0.02) and CRVE (β: −0.91, 95% confidence intervals: −1.62 to −0.20, P = 0.01). After magnification correction, this observation was no longer evident, regardless of the correction formula applied. When inappropriately assuming the fundus camera to be telecentric, we observed a bias toward increasing magnification-corrected CRAE and CRVE with increasing AL (β coefficients were positive or became more positive), reaching statistical significance (P < 0.05) for CRAE corrected using Bennett’s or Littmann’s formula, and for CRVE corrected using Bennett’s formula. Failing to correct for ocular magnification results in apparent narrowing of vessels in longer eyes, while inappropriate assumptions about telecentricity during magnification correction introduce an optical artifact that causes apparent widening of vessels. These findings suggest that myopic changes in retinal vessel caliber are optical (not biological) in nature. Proper correction of this effect to accurately derive dimensional measures is a crucial—yet often overlooked—methodological consideration in “oculomics” research investigating retinal biomarkers of systemic conditions. Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.